The Effect of Pair Passing and Individual Passing Drills on the Underhand Volleyball Passing Learning Outcomes of 10th Grade Students at SMKN 1 Koto Baru - Janiva, Yesi Wina; Prasetyo, Dian Estu; Sukron, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Physical education is an educational process that uses physical activity as a medium to achieve educational goals. Physical education is